Microsoft Office Accounting Express 2007 starter kit - Pierce, Pamela (Que, 2007)
Microsoft Office Accounting Express 2007 Starter Kit Set up Microsoft® Office Accounting Express 2007 quickly and painlessly! Microsoft Office Accounting Express 2007 will help you improve the way you manage your finances by reducing the time spent accounting for eBay sales and PayPal receipts, taking the worry out of payroll filing with ADP Payroll, and improving your bottom line by using Equifax credit profiles. Microsoft® Office Accounting Express 2007 Starter Kit provides clear and easy instructions on using Microsoft Office Accounting Express 2007 for all your daily business transactions-from invoicing to check writing. Introduction Chapter 1 A Microsoft Accounting Products Comparison Chapter 2 Downloading and Installing Chapter 3 Registration and Setup Wizard Chapter 4 Importing Data Chapter 5 Company Setup Chapter 6 Basic Accounting Transactions Chapter 7 Accounting Reports Chapter 8 End of Period Chapter 9 Advanced Features Appendix A Troubleshooting Glossary Author Bio Pamela Pierce is certified through Microsoft Professional Accountants' Network (MPAN) in Microsoft Small Business Accounting. She has been interviewed for articles on Microsoft Accounting 2007 in magazines such as Accounting Technology and Accounting Today. She is the owner of Empowering You!, a company that has been transforming businesses through technology since 1993. She is a college instructor in PC repair and maintenance and was one of the first Microsoft Partners and Microsoft Certified Solution Developers. www.quepublishing.com CD Info The full version of Microsoft Office Accounting Express 2007 is included on the accompanying CD! You're ready to start setting up and managing your accounting processes the minute you open the Starter Kit. · Shows how to use Microsoft Office Accounting Express 2007 with other Microsoft Office products, including Word, Excel, Access, and Outlook Business Contact Manager. · Provides clear and easy instructions on invoicing, deposits, check writing, and much more. · Shows how to customize forms and reports to fit your unique business. · Provides valuable setup tips. Set it up right, and you'll love it! Set it up incorrectly, and you'll have problems from the start. · Explains the import process from Intuit QuickBooks, Microsoft Money, and Microsoft Excel. · Includes a chapter on troubleshooting, plus many insider tips, notes, and cautions throughout all chapters. · Shows you ho ...
Print version record
Keywords: Microsoft Office; Accounting -- Software; Accounting -- Computer programs; Accounting; Software; Accounting; Computer programs; Accounting; Software